Reproductive biology of Oxychilus(Atlantoxychilus) spectabilis (Milne-Edwards, 1885) (Gastropoda: Pulmonata) : a gametogenic approach - Ferreira, Ana Filipa (2013)
The taxonomic status and anatomy of Oxychilus (Atlantoxychilus) spectabilis (Milne-Edwards, 1885), an endemic land snail from Santa Maria Island, Azores, has been subject of detailed study, yet information about its life history is wanting. This study describes the reproductive cycle of O. (A.) spectabilis and assesses the validity of three morphometric shell parameters as maturation diagnostic characters. Our results indicate that individuals are reproductively more active from May to November. However, the availability of spermatozoa throughout the year and the residual values of mature oocytes during the remaining months seem to provide minimum conditions for reproduction all year round. The snail has a functional protandric tendency and gonadal maturation is initially triggered by photophase and after regulated by temperature. The positive correlation between gonadal maturation and morphometric shell characters indicate that these parameters might be a useful tool for the diagnosis of snail’s maturation.